2009
DOI: 10.1146/annurev.physchem.59.032607.093719
|View full text |Cite
|
Sign up to set email alerts
|

DNA Excited-State Dynamics: From Single Bases to the Double Helix

Abstract: Ultraviolet light is strongly absorbed by DNA, producing excited electronic states that sometimes initiate damaging photochemical reactions. Fully mapping the reactive and nonreactive decay pathways available to excited electronic states in DNA is a decades-old quest. Progress toward this goal has accelerated rapidly in recent years, in large measure because of ultrafast laser experiments. Here we review recent discoveries and controversies concerning the nature and dynamics of excited states in DNA model syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

28
1,068
8
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 790 publications
(1,112 citation statements)
references
References 112 publications
(94 reference statements)
28
1,068
8
8
Order By: Relevance
“…It has been suggested that differences in In solution, additional long-lived dynamics (10s -100s ps) observed in transient absorption spectra of d(A) n -(n ≥ 2) have been assigned to the formation of excimer states that are delocalised over two (or more) adjacent π-stacked bases. 2,3,[38][39][40] In our data, no evidence for the formation of long-lived states, excimer or otherwise has been observed. There may be several reasons for the lack of excimer dynamics observed.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…It has been suggested that differences in In solution, additional long-lived dynamics (10s -100s ps) observed in transient absorption spectra of d(A) n -(n ≥ 2) have been assigned to the formation of excimer states that are delocalised over two (or more) adjacent π-stacked bases. 2,3,[38][39][40] In our data, no evidence for the formation of long-lived states, excimer or otherwise has been observed. There may be several reasons for the lack of excimer dynamics observed.…”
contrasting
confidence: 70%
“…1 Despite the efficient UV absorption, mediated by the optically bright 1 ππ* states localised on the four DNA nucleobases, the photodamage quantum yield in DNA is low (<1%). 2,3 This photostability is governed by the non-radiative decay mechanisms that enable the nucleobases to assimilate and dispose of the potentially harmful electronic energy in a non-destructive fashion.Gaining a molecular level understanding of these processes has been a long-standing goal, not only because of its role in radiation damage of DNA, but also to assess why nature has evolved using such a select number of molecular building blocks to define the genetic code. 4 Much of the experimental effort has been devoted to the fate of adenine (Ade) following excitation to its 1 ππ* states.…”
mentioning
confidence: 99%
“…[4][5][6] As such, the DNA and RNA nucleobases are classed as photostable species. From a photochemistry perspective, photostability is often characterized by short (<1 ps) electronically excited state lifetimes, low fluorescence quantum yields (Φf < 10 -4 ) and a strong resistance to the formation of undesired and potentially harmful photoproducts.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Solvent effects on the photochemistry of nucleotide bases have been widely studied. In particular, the high sensitivity of the excited states of uracil to a solvent has made it a popular system for studying photochemistry.…”
Section: Introductionmentioning
confidence: 99%